If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13=7+3p
We move all terms to the left:
13-(7+3p)=0
We add all the numbers together, and all the variables
-(3p+7)+13=0
We get rid of parentheses
-3p-7+13=0
We add all the numbers together, and all the variables
-3p+6=0
We move all terms containing p to the left, all other terms to the right
-3p=-6
p=-6/-3
p=+2
| 8=g=16/4 | | c-(-5)=8 | | 1/2(8x+8)=24. | | 8n+8-6n=2n+8 | | 7s+3=4s+6 | | n-35/5=7 | | k/5-6=6 | | 18=9+3k | | x+.3x=112982 | | y+298=489 | | p-90/4=2 | | 38=4(u+2)-7u | | 24=3(n-5)24=3(n−5 | | 6r+19=19 | | 2j-7=5 | | -40=m/2+10 | | $x^2-13x+4=0$. | | 6(t-4)=2(t+3) | | 4(2x-3)=6(3x+1) | | 6y-3=5y+2 | | M=8n+12 | | 4(2x-3=6(3x+1) | | z-11=2.2 | | 560=114+d | | 3n-8=5n+12 | | 18x-20=34 | | x/11-3=16 | | 18x+321=1059 | | 3-2(x+1)=25 | | 7(d-3)=-28 | | -2y+10=22 | | 90+x=120 |